Standard Operating Procedure Pemutusan Hubungan Kerja (PHK) Menurut Undang-Undang Ketenagakerjaan No. 13 Tahun 2003 di kota Medan - Herlina Hanum Harahap; Roy Samuel Fernandus (Mahesa Research Center, 2026)
Termination of employment is Termination of Employment (PHK) is the termination of the relationship between the employee and the employer which results in the termination of the rights and obligations of both parties. Layoffs can occur due to various things, both caused by employees (such as resignation) and by the company (such as business reasons or court decisions), in accordance with the provisions of the labor law. The problem in this study is how to the SOP for termination of employment according to the labor law number 13 of 2003. This research method uses normative juridical research methods. The normative juridical method is a method whose research uses library research, books, journals, and labor law number 13 of 2003. The results of the research in the laws and regulations of each termination of employment have different SOPs. In Law No. 13 of 2003, the SOP for termination of employment must meet the applicable requirements, for example, if there is a mistake against the employee, the employee must be reprimanded first before laying off.